Suppression of Maize (Zea mays) Seedling Growth by Invasive Alligatorweed (Alternanthera philoxeroides) Residues - NADEEM,M. (2017)
ABSTRACT: To investigate the allelopathic influence of soil incorporated plant residues of alligatorweed on emergence and seedling growth of maize (Zea mays), an experiment was conducted under laboratory conditions in the 2014-15 period. The effect of soil amended with whole plant residues of alligatorweed at different concentrations (1, 2, 3, 4 and 5% on w/w basis) was compared with residue free soil (control). Emergence traits, such as emergence percentage, time to 50% emergence, mean emergence time and emergence index were negatively influenced by weed residue incorporation as compared with weed residue free soil. Alligatorweed residues also exerted a pronounced negative influence on root and shoot lengths, root and shoot dry weights and seedling vigor index of the maize crop. The results revealed that the inhibitory effect was directly proportional to the increasing concentrations (1, 2, 3, 4 and 5%) of the weed residues as compared to control treatment. It was observed that soil infested with 4% and 5% residues of alligatorweed caused a maximum reduction in emergence (76-87%), root and shoot lengths (58-73% and 42-61%), root and shoot dry weights (49-58% and 40-48%) and seedling vigor index (87-95%) of the maize crop. Chlorogenic acid, ferulic acid, 4-hydroxy-3-methoxybenzoic acid, trans-4-hydroxy 3-methoxy cinnamic acid, gallic acid, p-coumaric acid, querceitin and syringic acid were identified as water soluble phenolics in alligatorweed residue soil saturated solution. This study indicates that the allelopathic potential of alligatorweed may play an important role in suppressing maize seedling growth.